PENINGKATAN HASIL BELAJAR BAHASA JAWA GEGURITAN MELALUI METODE THINK PAIR SHARE PADA SISWA KELAS XI IPA 2 SMAN 1 WEDI KABUPATEN KLATEN - Kinasih_yuliastuti Kinasih; Bayu Indrayanto (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
This study aims to improve student learning outcomes in Javanese language subjects, the subject of geguritan in class XI IPA 2 SMAN 1 Wedi, Klaten Regency. The research method used is the classroom follow-up research method (CAR). This classroom action research consists of four steps, namely planning, action, observation and reflection. Furthermore, to examine the possibility of learning success, the Think Pair Share method is used. The results showed success. The data shows an increase from the pre-cycle stage to the second cycle. The success of the research is in accordance with the success indicators obtained during the second cycle, namely 85% of students complete the KKM.